ChemInform Abstract: Substrate and Catalyst Effects in C—H Insertion Reactions of α‐Diazoacetamides. Issue 52 (6th December 2016) - Ring, Aoife; Ford, Alan; Maguire, Anita R.
Abstract: Review: 66 refs.